Absence of toughening behavior in 0.94(Na1/2Bi1/2)TiO3-0.06BaTiO3 relaxor ceramic. (15th July 2017) - Vögler, M.; Daniels, J.E.; Webber, K.G.; Rödel, J.
Abstract: The fracture behavior of the unpoled 0.94(Na1/2 Bi1/2 )TiO3 -0.06BaTiO3 relaxor ferroelectric was investigated. Previous studies indicated that a metastable ferroelectric long-range order can be induced by mechanical stresses, which could lead to a crack tip process zone and increasing crack resistance during crack growth. Crack propagation in compact tension samples yielded a constant crack resistance as function of crack length. This is consistent with ex situ x-ray diffraction experiments, where a remanent induced process zone on the fracture surface could not be detected. We suggest the very high transformation stress, determined via macroscopic stress-strain measurements, is responsible for the absence of toughening. Graphical abstract: